2017
DOI: 10.1111/sltb.12366
|View full text |Cite
|
Sign up to set email alerts
|

Mass Killings in the United States from 2006 to 2013: Social Contagion or Random Clusters?

Abstract: In line with previous research on suicide and social contagion, there has been widespread speculation that mass killings-which often involve suicidal offenders-are socially contagious for up to 14 days. This study tested these claims by making comparisons (i) between observed chronological clusters of mass killings in the United States from 2006 to 2013 and clusters in 500 simulations containing 116,000 randomly generated dates, and then (ii) between observed mass killings receiving varying levels of public at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 23 publications
(38 reference statements)
0
29
1
Order By: Relevance
“…Consistent with the growing literature, we define a mass public shooting as an incident of targeted violence where an offender has killed or unequivocally attempted to kill four or more victims on a public stage (e.g., workplace, schools, parks, and businesses) in one or multiple closely related locations within a 24-h period (2)(3)(4)(5)(6)(7)(9)(10)(11)(12). Both familicides and felony-related mass shootings are excluded from this operationalization (12).…”
Section: Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the growing literature, we define a mass public shooting as an incident of targeted violence where an offender has killed or unequivocally attempted to kill four or more victims on a public stage (e.g., workplace, schools, parks, and businesses) in one or multiple closely related locations within a 24-h period (2)(3)(4)(5)(6)(7)(9)(10)(11)(12). Both familicides and felony-related mass shootings are excluded from this operationalization (12).…”
Section: Definitionsmentioning
confidence: 99%
“…Consistent with most studies on the subject (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(14)(15)(16)(17)(18)(19), we employed an open-source data collection strategy to identify and collect information on both failed and successful mass public shootings that occurred in the United States from 1966 to 2017. Open-source data are information that is open to the public (20).…”
Section: Data Collection Strategymentioning
confidence: 99%
“…For instance, Kissner () found that the occurrence of a mass public shooting significantly increased the hazard of experiencing another mass public shooting for 2 weeks. However, Lankford and Tomek () found no evidence of such a short‐term contagion effect. Capellan () did not find evidence of contagion; rather, he found that the occurrence of a mass public shooting has a deterrent effect on future ones.…”
Section: Discussionmentioning
confidence: 99%
“…As an example of the advantages of unbinned likelihood methods in increasing the statistical power of an analysis, here we compare and contrast two recent analyses of contagion in mass killings in America, both of which were based on exactly the same data, but used different methodology. One concluded that there was evidence of contagion in mass killings [ 6 ], while the later analysis contradicted this claim [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using the same data presented in Towers et al (2015), Lankford & Tomek (2017) published a subsequent analysis that claimed to find no significant evidence of contagion in mass killings [ 7 ]. They primarily based their conclusion on a simple analysis of how many events occurred within 14 days of a prior event, under the null hypothesis assumption that the data were randomly Uniformly distributed in time.…”
Section: Introductionmentioning
confidence: 99%